APPLICATION OF ADVANCED MECHANICAL MODELS FOR DESIGN AND CONSTRUCTION OF DIKES, REVETMENTS, EMBANKMENTS AND PORT YARD IN NAM DINH VU - HAI PHONG AREA - Duong, Nguyen Thi Bach (Vietnam Journal of Marine Science and Technology, 2018)
To apply advanced models for design and construction of dykes, revetments, embankments and port yard in Nam Dinh Vu - Hai Phong area, it is necessary to determine parameters of these models such as Hardening Soil Model (HS) and Soft Soil Model (SS). These can be determined through correlation parameters by available soil test as the fastest approach if we do not have direct experiments. This article defines and predicts the soil characteristics of the HS and SS in Nam Dinh Vu site, additionally it introduces the application of these parameters to the design of a typical dike section of Nam Dinh Vu dike.